Small Firms' Formalisation : The Stick Treatment - De Giorgi, Giacomo (Taylor and Francis, 2018)
Firm informality is pervasive throughout the developing world, Bangladesh being no exception. The informal status of many firms substantially reduces the tax basis and therefore impacts the provision of public goods. The literature on encouraging formalization has predominantly focused on reducing the direct costs of formalization and has found negligible impacts of such policies. In this paper, we focus on a stick intervention, which to the best of our knowledge is the first one in a developing country setting that deals with the most direct and dominant form of informality, that is registration with the tax authority with a direct link to the country’s potential revenue base and thus public goods provision. We implement an experiment in which randomly selected firms are visited by tax representatives who deliver an official letter from the Bangladesh National Tax Authority stating that the firm is not registered and the consequential punishment if the firm fails to register. We find that the intervention increases the rate of registration among treated firms, while firms located in the same market but not treated do not seem to respond significantly. We also find that only larger revenue firms at baseline respond to the threat and register. Our findings have at least two important policy implications: i) the enforcement angle, which could be an important tool to encourage formalization; and ii) targeting of government resources for formalization to high-end informal firms. The effects are generally small in levels and this leaves open the question of why many firms still do not register.